1990
DOI: 10.1073/pnas.87.21.8398
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox gene expression plus autocrine growth factor production elicits myeloid leukemia.

Abstract: In the murine myelomonocytic leukemia WEHI-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 33 publications
3
98
0
Order By: Relevance
“…Much of this evidence comes from surveys that demonstrate increased expression of HOX genes and/or their regulators in a broad range of solid tumors (Celetti et al, 1993;Cillo, 1994) and leukemias (Look, 1997). In addition, overexpression of several HOX genes leads to either expansion of particular hematopoietic compartments Crooks et al, 1999) or to overt cellular transformation (Perkins et al, 1990;Thorsteinsdottir et al, 1997;Kroon et al, 1998). Several previous studies showed that enforced expression of the HOXB4 protein resulted in hyperproliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this evidence comes from surveys that demonstrate increased expression of HOX genes and/or their regulators in a broad range of solid tumors (Celetti et al, 1993;Cillo, 1994) and leukemias (Look, 1997). In addition, overexpression of several HOX genes leads to either expansion of particular hematopoietic compartments Crooks et al, 1999) or to overt cellular transformation (Perkins et al, 1990;Thorsteinsdottir et al, 1997;Kroon et al, 1998). Several previous studies showed that enforced expression of the HOXB4 protein resulted in hyperproliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for a functional role of Hox genes in the hematopoietic system was initially provided by the finding that Hoxb-8 is deregulated in myeloid leukemia cells [9,10] and that elevated Hoxb-8 expression leads to alterations in myeloid differentiation [11]. Retroviral infection of Hoxb-8 into murine bone marrow cells results in leukemia after transplantation into irradiated hosts [12]. Subsequently, it has been shown that pathological aberrations in the hematopoietic system can be caused by deregulated expression of a number of homeobox genes, including HOXA10 [13], HOXB3 [14], and HOXB4 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations in Hox gene expression pro®le have been associated with leukemic transformation. For example, the WEHI-3B leukemic cell line most likely originated from proviral insertional activation of Hoxb8 and interleukin-3 (IL-3) (Blatt et al, 1988), since retroviral over-expression of these two genes in murine bone marrow cells causes an aggressive polyclonal acute leukemia, whereas neither gene alone is acutely transforming (Perkins et al, 1990). Furthermore, a high proportion of mice transplanted with bone marrow cells over-expressing Hoxb8, or Hoxa10 or Hoxb3 eventually develop an acute myeloid leukemia after a latency period of several months (Perkins and Cory, 1993;Thorsteinsdottir et al, 1997;Sauvageau et al, 1997).…”
Section: Introductionmentioning
confidence: 99%